2014
DOI: 10.1680/macr.13.00301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the composition of powder-type SCC on conversion factors for compressive strength

Abstract: Depending on practical considerations and standards, different types of test specimens are used for the determination of the uniaxial compressive strength of concrete. Appropriate conversion factors, also referred to as shape factors, are needed to convert the compressive strength as determined on one type of specimen to the equivalent compressive strength of another type of specimen. As such shape factors for vibrated concrete are influenced by the composition of the concrete, questions arise concerning the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Fifteen cubes (with side 100 mm or 150 mm) and four cylinders (with height 200 mm and diameter 100 mm) were produced per mix according to EN 206:2013+A1:2016 [39] and resulting in a total of 152 specimens to test mechanical properties and durability. According to research of Van Der Vurst et al [40], in case of high strength concrete, it is considered that the shape/size factor between cubes with side 100 mm and cubes with side 150 mm is more or less equal to one.…”
Section: Concrete Levelmentioning
confidence: 99%
“…Fifteen cubes (with side 100 mm or 150 mm) and four cylinders (with height 200 mm and diameter 100 mm) were produced per mix according to EN 206:2013+A1:2016 [39] and resulting in a total of 152 specimens to test mechanical properties and durability. According to research of Van Der Vurst et al [40], in case of high strength concrete, it is considered that the shape/size factor between cubes with side 100 mm and cubes with side 150 mm is more or less equal to one.…”
Section: Concrete Levelmentioning
confidence: 99%
“…The compressive strength in the structure was thus represented by a log‐normally distributed variable with mean μc=0.85·0.87·1.00·μnormalc,normalcube0.74exp()normalE[]y and coefficient of variation. Vc=0.062+0.052+Vnormalc,cube20.006+VAR[]y assuming that Equations and are valid approximations. It should be noted that the ratio between the cylinder and cube strength also has a significant coefficient of variation which should be taken into account in Equation if a detailed strength prediction is necessary. However, for the present application examples, the nominal ratio was assumed sufficient.…”
Section: Application Examplesmentioning
confidence: 99%
“…Foster et al report from a study on a collection of strength recordings from Australia, and it can be shown that the 28‐day compressive strength of lab‐cured cylinders can be represented by a normally distributed variable with mean μ c =1.21 f ck and a coefficient of variation of V c =0.12. Correlation with other material parameters for concrete can be found elsewhere, and the relation between cylinder and cube strength is discussed in several contributions …”
Section: Introductionmentioning
confidence: 99%